2021
DOI: 10.2196/26769
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Depression Trends on Twitter During the COVID-19 Pandemic: Observational Study

Abstract: Background The COVID-19 pandemic has affected people’s daily lives and has caused economic loss worldwide. Anecdotal evidence suggests that the pandemic has increased depression levels among the population. However, systematic studies of depression detection and monitoring during the pandemic are lacking. Objective This study aims to develop a method to create a large-scale depression user data set in an automatic fashion so that the method is scalable and can be adapte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 66 publications
2
65
0
Order By: Relevance
“…Saleh et al [ 41 ] attempted to understand public perception of COVID-19 social distancing on Twitter, and Xue et al [ 42 ] analyzed users’ discourse and psychological reactions to the pandemic on Twitter. Other studies focused on specific populations, for example, US governors and presidential cabinet members [ 7 ], the social media activity and mental health of students in Switzerland [ 8 ], detection of users who were found to suffer from depression using transformer-based deep learning models on the Twitter platform [ 43 ], among others. Recently, Ojo et al [ 9 ] examined the behavior of health care workers on social media concerning two specific public health crises—the COVID-19 pandemic and gun violence—using analysis of two online discussions derived from two selected hashtags.…”
Section: Discussionmentioning
confidence: 99%
“…Saleh et al [ 41 ] attempted to understand public perception of COVID-19 social distancing on Twitter, and Xue et al [ 42 ] analyzed users’ discourse and psychological reactions to the pandemic on Twitter. Other studies focused on specific populations, for example, US governors and presidential cabinet members [ 7 ], the social media activity and mental health of students in Switzerland [ 8 ], detection of users who were found to suffer from depression using transformer-based deep learning models on the Twitter platform [ 43 ], among others. Recently, Ojo et al [ 9 ] examined the behavior of health care workers on social media concerning two specific public health crises—the COVID-19 pandemic and gun violence—using analysis of two online discussions derived from two selected hashtags.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that all of the three mental health problems (stress, anxiety, and loneliness) increased in 2020. Another study developed a transformer-based model to monitor the depression trend using Twitter [33]. The results showed that there was a significant increase in depression signals when the topic is related to COVID-19.…”
mentioning
confidence: 99%
“…Linguistic analyses showed that people express more concerns in terms of the COVID-19 crisis. Zhang et al [118] built a fusion classifier that integrated DL model, psychological text features, and demographic information to investigate the relationships between feature and depression signals. The proposed model demonstrated an accuracy of 78.9% and has been used to analyze the depression level of different groups of people on Twitter in terms of three US states (New York, California, and Florida).…”
Section: Ai In Covid-19 On Behavioral and Social Sciencesmentioning
confidence: 99%